2021
DOI: 10.1111/ijd.15814
|View full text |Cite
|
Sign up to set email alerts
|

Role of antimicrobial peptides in atopic dermatitis

Abstract: Host defense peptides (HDPs) or antimicrobial peptides (AMPs) are short cationic amphipathic peptides of divergent sequences, which are part of the innate immune system and produced by various types of cells and tissues. The predominant role of HDPs is to respond to and protect humans against infection and inflammation. Common human HDPs include defensins, cathelicidin, psoriasin, dermcidin, and ribonucleases, but these peptides may be dysregulated in the skin of patients with atopic dermatitis (AD). Current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…On day 3, the increases were 9.5-, 8.8-, and 6.5-fold for cBD1, cBD3, and cCath, respectively, and on day 10, the respective increases were 9.0-, 5.0-, and 8.0-fold. These findings resemble the dysregulation of HDPs that has been reported in human AD and psoriasis: in data for both AD and psoriasis subjects, protein expression levels of the antimicrobial peptides (AMPs) RNase 7, hBD-2, and hBD-3 were all increased compared to levels in healthy matched controls (Harder et al, 2010;Suwanchote et al, 2022). These similar canine and human findings support the use of the canine model in further elucidating the role of HDPs in AD.…”
Section: In Vivo Skin Barrier Defect Modelsupporting
confidence: 81%
“…On day 3, the increases were 9.5-, 8.8-, and 6.5-fold for cBD1, cBD3, and cCath, respectively, and on day 10, the respective increases were 9.0-, 5.0-, and 8.0-fold. These findings resemble the dysregulation of HDPs that has been reported in human AD and psoriasis: in data for both AD and psoriasis subjects, protein expression levels of the antimicrobial peptides (AMPs) RNase 7, hBD-2, and hBD-3 were all increased compared to levels in healthy matched controls (Harder et al, 2010;Suwanchote et al, 2022). These similar canine and human findings support the use of the canine model in further elucidating the role of HDPs in AD.…”
Section: In Vivo Skin Barrier Defect Modelsupporting
confidence: 81%
“…Host defence peptides (HDPs), or antimicrobial peptides (AMPs), as one of the critical parts of the immune system, can effectively inhibit the pathogenesis of infections and protect the host from inflammation 6 . However, the production of these peptides is often dysregulated by the microbes and inflammatory molecules present in AD lesions 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of these peptides is often dysregulated by the microbes and inflammatory molecules present in AD lesions 7–9 . Recently, research on human HDPs indicate they have some potential advantages for AD treatment, such as their broad spectrum antibacterial action and their immunomodulatory effects, making them a promising candidates in AD patients' management 6 . Amphibians, found in both terrestrial and aquatic environments rich in microbes, are considered excellent natural sources of HDPs/AMPs 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, AMPs such as hBDs, LL-37, and S100A7 have been reported to improve the TJ barrier in vitro in keratinocyte monolayers [ 24 , 25 , 26 , 27 ]. Although accumulated evidence implies a promising role for AMPs in the treatment of AD [ 11 , 40 , 44 ], the precise role of AMPs in the immunopathogenesis of AD remains elusive. In this study, our microarray analysis revealed that the gene expression of IGFBP-5, the parent protein of AMP-IBP5, is lower in skin lesions of patients with AD than in non-lesional skin, suggesting that AMP-IBP5 might be involved in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%